Congenital peritoneopericardial diaphragmatic hernia in a family of Persian cats. Issue 2 (October 2018) - Margolis, Carol; Zakošek Pipan, Maja; Demchur, Jolie; Or, Matan; Henthorn, Paula; Casal, Margret L
Case series summary: The congenital midline defects of peritoneopericardial diaphragmatic hernia (PPDH) and omphalocele are believed to be related developmental defects, and have both been described in cats and dogs. This case series describes multiple cases of PPDH and omphalocele in related cats. The majority of cats affected with midline defects (PPDH or omphalocele) were male, consistent with previous reports of male overrepresentation. Relevance and novel information: This is the first report of a family of Persian cats affected by PPDH and/or omphalocele. Clinical findings and pedigree information are suggestive of an autosomal recessive mode of inheritance. However, other modes of inheritance cannot be ruled out owing to limited sample size. The findings in this family and previous reports of Persians affected by PPDH warrant further investigation. Based on this information, recommendations for breeding populations of Persians and long-haired cats should include thoracic radiographs to screen for PPDH until a DNA-based genetic test is available.